Pembelajaran Materi Garis Bilangan dengan Berbantuan Alat Peraga Number Line pada Siswa Sekolah Menengah Pertama - Agna Ilma Taofik; Faizah Nurwita; Muhammad Ridha; Norma Septiani; Peni Fauziah Puadah; Muhammad Azhari Panjaitan; Qania Agustika Siagian; Dadang Juandi; Elah Nurlaelah (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Number line material is an essential material in learning mathematics. However, in fact some students experience difficulties in the learning process of number line material. As was found among students at the Graha Asuh Jabal 165 Foundation, only seven of twenty five children said they liked mathematics at the Al-Hilal 3 Sarijadi Foundation. Based on the problems found, this service activity aims to help students understand number line material. The method for implementing this activity consists of three stages, namely: (1) the activity planning stage; (2) implementation stage; and (3) evaluation stage. The results obtained in this service activity are in the form of post-test results which show that there is an increase in student responses from the results of the pre-test conducted at the beginning of learning.